Recurrent ovarian steroid cell tumour not otherwise specified: A case report - Azmaniza Baharudin (Clinical Case Reports, 2021)
Abstract Steroid cell tumors not otherwise specified are one of the rare virilizing ovarian tumors. Most of the tumors are benign. This case report illustrates the challenge in managing steroid cell tumor not otherwise specified, which starts from determining its malignant potential, surveillance, and adjuvant treatment option.